Young learners - Phillips, Sarah (Oxford University Press Oxford, 2006)
Young Learners (Resource Books for Teachers) by Alan Maley is a practical resource designed to support teachers in the classroom when working with young learners. The book offers a variety of engaging activities, techniques, and methodologies aimed at helping teachers foster language development in children. It provides structured lesson plans and adaptable materials, with an emphasis on making learning enjoyable and effective for younger students. Key areas include promoting communicative competence, developing language skills through play, and incorporating cultural awareness in language education. The book is part of the Resource Books for Teachers series, which focuses on practical teaching solutions across a range of language learning contexts.